A biblioteca pública como fator de inclusão social e digital: um estudo da Biblioteca Parque de Manguinhos - Silva, Aline Gonçalves da (2012)
This dissertation focuses on the issue of digital inclusion in public libraries and selects a public library installed in a poor neighborhood in the city of the Rio de Janeiro as a study object